Deliberate Entanglements. - Kester, Bernard; Wight, Frederick S. (Los Angeles : UCLA Art Galleries, University of California, 1971)
Abakanowicz, Magdalena ; Al-Hilali, Neda ; de Amaral, Olga ; Beutlich, Tadek ; Buic, Jagoda ; Grossen, Françoise ; Hicks, Sheila ; Jacobi, Ritzi & Peter ; Munoz, Aurelia ; Nottingham, Walter ; Sekimachi, Kay ; Zachai, Dorian ; Zeisler, Claire
biografie
Deliberate Entanglements: an exhibition of fabric forms organized by the UCLA Art Galleries, University of California, Los Angeles. Participants: Portland Art Museum, Vancouver Art Gallery, Utah Museum of Fine Arts, Salt Lake City, California Palace of the Legion of Honor, San Francisco, 1971-1972
Engels
boek